DETERMINAN NILAI PERUSAHAAN PADA MISCELLANEOUS INDUSTRY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Carina Florencia; Beny Beny (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
This research aims to determine the effect of profitability, leverage, liquidity, firm size, and asset structure on firm value. The population used in this research is Miscellaneous Industry companies listed on the Indonesia Stock Exchange for the 2012-2020 period. The sampling method used in this research is purposive sampling method with a total sample of 12 companies. This research uses causal research to determine the effect between the independent variable and the dependent variable and Multiple Regression Analysis to analyze the data. Based on the results of the research conducted, it can be concluded that profitability has effect on firm value, so that profitability can increase the firm value and vice versa. Leverage has effect on firm value, it means that the use of debt can increase the firm value. Liquidity has effect on firm value, the higher liquidity will increase the firm value. Firm size has effect on firm value, the bigger company can decrease the firm value. Asset structure has effect on firm value, the greater asset structure will decrease the firm value and vice versa.